Tingkat Keterampilan Teknis Dasar Permainan Sepakbola Siswa U-14 Sekolah Sepakbola Luwu Kabupaten Luwu - Asri Awal; Muh Syachrul Syamsuddin; Irwin (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
Type your abstract here up to 300 words. Font type is “Times” with size 9. State the summary of Introduction, objectives, method, findings, conclusion, and recommendation. Based on the results of the survey analysis on the level of basic technical skills in soccer games for U-14 students at Luwu Soccer School, Luwu Regency, from the test data, the percentage of shooting data has a percentage, namely 5 people who fall into the Very Low criteria with a percentage of 25%. 10 people who fall into the Low criteria with a percentage of 50%, 3 0people who fall into the Medium criteria with a percentage of 15%. and 2 people who fall into the Good criteria with a percentage of 10%. Dribling ability has a percentage, namely 17 people who fall into the Very Low criteria with a percentage of 85%. 3 people who fall into the Low criteria with a percentage of 15%. Passing ability has a percentage, namely 7 people who fall into the Low criteria with a percentage of 35%. 6 people who fall into the Moderate criteria with a percentage of 30%, 7 0people who fall into the Good criteria with a percentage of 35%. Heading ability has a percentage, namely 1 person who falls into the Very Low criteria with a percentage of 5%. 9 people who fall into the Low criteria with a percentage of 45%, 3 0people who fall into the Medium criteria with a percentage of 15%. and 7 people who fall into the Good criteria with a percentage of 35%. overall sample 20.